2009
DOI: 10.1021/ef900959r
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Variations between Precipitated and Organic Solid Deposition Control (OSDC) Asphaltenes and the Effect of Inhibitors on Deposition by Electrospray Ionization Fourier Transform Ion Cyclotron Resonance (FT-ICR) Mass Spectrometry

Abstract: Organic solid deposition control (OSDC) is a live oil test capable of simulating the production conditions of oil streams and can generate asphaltene deposits under production system conditions. OSDC can also simulate gas lift conditions because the producers are looking for artificial lift methods to produce oil from low-energy reservoirs. In this paper, we present the first compositional study on the OSDC deposits under gas lift conditions and compare it to C7 asphaltenes from the same crude oil precipitated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…In other studies, it was shown that the addition of asphaltene inhibitors did not necessarily prevent or reduce the deposition. However, in some cases, it worsened the problem. ,, …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In other studies, it was shown that the addition of asphaltene inhibitors did not necessarily prevent or reduce the deposition. However, in some cases, it worsened the problem. ,, …”
Section: Discussionmentioning
confidence: 99%
“…Although dispersion tests have been widely used as fast screening methods for asphaltene inhibitors, there is no proven correlation between the dispersive efficiency and the prevention of asphaltene deposition on metallic surfaces. ,,, According to Vargas et al, the aggregation and deposition of particles to the surface are two competing phenomena. Thus, reducing the aggregation of asphaltene particles might facilitate the deposition process under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al () oxidized sulfides in petroleum and identified them using (+)‐ESI FT‐ICR MS (Liu et al, ). ESI is one of the major ionization techniques used to study crude oils and there have been a number of publications using this technique for oil analyses (Zhan & Fenn, ; Hughey et al, ; Qian et al, 2001a,b; Hughey, Rodgers, & Marshall, ; Barrow et al, 2003, 2009; Hemmingsen et al, ; Klein et al, ; Mullins et al, ; Stanford et al, 2006, 2007a,b; Teräväinen et al, ; Headley et al, ; Panda et al, ; Schaub et al, ; Mapolelo et al, ; Miyabayashi et al, ; Smith et al, 2008a,b; Da Campo et al, ; Juyal et al, 2009, 2010; Shi et al, 2009, 2010a,b; Liu et al, ; Zhang et al, 2010, 2011; Zhu et al, ; Li et al, ; Chen et al, ; Gaspar et al, ; Jin, Kim, & Birdwell, ).…”
Section: Study Of Ionization Methodsmentioning
confidence: 99%